ANALISIS POSTER VIDEO KLIP LATHI : KAJIAN SEMIOTIKA FERDINAND DE SAUSSURE - Sitompul, Anni Lamria; Patriansah2, Mukhsin; Pangestu, Risvi (UNIVERSITAS INDO GLOBAL MANDIRI)
Occasionally, communication continues to develop, ranging from the use of smoke signals, drums, paper inventions, telegraphs, telephones, computers, emails to the internet as a medium of communication. One of the communication media that is developing today is posters. Posters used to convey messages or information to the public are generally printed and placed in public area or through social media. The visual markings used by the designer in the poster are addressed to the public so that the public can understand the message and the purpose of the information. The use of poster visual marks from the video clip of the song